2021
DOI: 10.1515/jbcpp-2020-0405
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glutaraldehyde on the characteristics of bovine hydroxyapatite-gelatin based bone scaffold as gentamicin delivery system

Abstract: Objectives Biomaterials are widely used as drug delivery systems targeting bone tissue, such as to treat bone infectious disease. However, the addition of drugs to biomaterials weakens their mechanical properties. Crosslinkers are compounds that improve the mechanical properties of biomaterials. This study aims to determine the effect of glutaraldehyde (GTA) as a crosslinker on the characteristics of bovine hydroxyapatite-gelatin-based bone scaffold with gentamicin as antibiotics (BHA-GEL-GEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…17 Bovine hydroxyapatite (BHA) is natural hydroxyapatite extracted from bovine bone. 6,19,20 BHA has similar characteristics to human bone, one of which BHA contains a carbonate substitution group similar to human HA, which is not found in synthetic HA. 19,21 It has been reported that HA-containing carbonate (carbonated HA) increases osteoblast proliferation, thereby accelerating the synthesis of new bone.…”
Section: Introductionmentioning
confidence: 99%
“…17 Bovine hydroxyapatite (BHA) is natural hydroxyapatite extracted from bovine bone. 6,19,20 BHA has similar characteristics to human bone, one of which BHA contains a carbonate substitution group similar to human HA, which is not found in synthetic HA. 19,21 It has been reported that HA-containing carbonate (carbonated HA) increases osteoblast proliferation, thereby accelerating the synthesis of new bone.…”
Section: Introductionmentioning
confidence: 99%
“…These activities also contributed to the use of ginger as a medicinal plant 24,31 . Bone diseases such as bone defects, osteoporosis, and osteoarthritis are challenging to treat [32][33][34][35][36][37] . Osteoporosis is a bone disease that occurs when the body constantly absorbs and replaces bone tissue, resulting in weak and brittle bone [1][2][3] .…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma also causes large bone defects prone to self-healing, resulting in movement restrictions and negatively impacting the patient's quality of life. [ 1 2 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%